2013
DOI: 10.1165/rcmb.2012-0174oc
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 and Prostaglandin E Receptor 3 Receptors Mediate Global Airway Contraction after Local Epithelial Injury

Abstract: Epithelial injury and airway hyperresponsiveness are prominent features of asthma. We have previously demonstrated that laser ablation of single epithelial cells immediately induces global airway constriction through Ca(2+)-dependent smooth muscle shortening. The response is mediated by soluble mediators released from wounded single epithelial cells; however, the soluble mediators and signaling mechanisms have not been identified. In this study, we investigated the nature of the epithelial-derived soluble medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
1
8
1
Order By: Relevance
“…PTGER3, the prostaglandin EP 3 receptor (EP 3 ), is one of four receptors for prostaglandin E 2 (PGE 2 ) and is involved in bronchoconstriction. 37,38 PTGER3 showed a counter regulation to miR-3935 as expected (Figure 4F, Figure S1E-F), which was underlined by the inverse correlation between miR-3935 and its predicted target PTGER3 (Figure 4G; r = −0.57; p = .0294).…”
Section: Ait-related Induction Of Mir-3935 Corresponds To Suppression Of Transcripts Of Its Target Ptger3supporting
confidence: 74%
See 2 more Smart Citations
“…PTGER3, the prostaglandin EP 3 receptor (EP 3 ), is one of four receptors for prostaglandin E 2 (PGE 2 ) and is involved in bronchoconstriction. 37,38 PTGER3 showed a counter regulation to miR-3935 as expected (Figure 4F, Figure S1E-F), which was underlined by the inverse correlation between miR-3935 and its predicted target PTGER3 (Figure 4G; r = −0.57; p = .0294).…”
Section: Ait-related Induction Of Mir-3935 Corresponds To Suppression Of Transcripts Of Its Target Ptger3supporting
confidence: 74%
“…On the other hand, 661 genes were predicted as targets of the upregulated miRs (Figure 4E, Table ; Figure ; Table ), of which only one gene (PTGER3) was also significantly downregulated on the mRNA level in the same samples. PTGER3, the prostaglandin EP 3 receptor (EP 3 ), is one of four receptors for prostaglandin E 2 (PGE 2 ) and is involved in bronchoconstriction 37,38 . PTGER3 showed a counter regulation to miR‐3935 as expected (Figure 4F, Figure E‐F), which was underlined by the inverse correlation between miR‐3935 and its predicted target PTGER3 (Figure 4G; r = −0.57; p = .0294).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Similar rapid responses have been observed in recent studies using ex vivo lung-tissue slices from rats, where local injury to a single epithelial cell triggered an instantaneous Ca 2+ wave throughout the epithelium and induced ASM contraction within several seconds that lasted for tens of seconds (54). It was observed that epithelial injury triggered the release of ATP, and airway contraction was completely blocked by selective inhibition of COX2 (55). While, in these studies, the ASM contraction was triggered by an injury to the epithelium, our study suggests that mechanically stimulating the epithelium can be sufficient to obtain similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that COX-2 induction in airway smooth muscle cells and COX-2-derived lung inflammation may be triggered also via PI3K/Akt/NF-κB pathway after activation of EGFR/PDGFR ). These receptors can be rapidly activated by adenosine released from injured epithelial cells, leading to immediate COX-2-mediated airway constriction (Zhou et al 2013). Taken together, in meconium-polluted airways where multiple agents including phospholipase A2 can directly damage epithelial cells, inhibition of NF-κB-dependent COX-2 induction may prevent prostanoid bronchoconstriction and improve oxygenation.…”
Section: Discussionmentioning
confidence: 99%